FXR and liver carcinogenesis - Huang Xiong-fei; Zhao Wei-yu; Huang Wen-dong (Acta Pharmacologica Sinica; Vol 36, No 1 (January 2015): Acta Pharmacologica Sinica(Special Feature:Nuclear Receptors: Biology, Structures, and Drug Discovery）, 2017)
Farnesoid X receptor (FXR) is a member of the nuclear receptor family and a ligand-modulated transcription factor. In the liver, FXR has been considered a multi-functional cell protector and a tumor suppressor. FXR can suppress liver carcinogenesis via different mechanisms: 1) FXR maintains the normal liver metabolism of bile acids, glucose and lipids; 2) FXR promotes liver regeneration and repair after injury; 3) FXR protects liver cells from death and enhances cell survival; 4) FXR suppresses hepatic inflammation, thereby preventing inflammatory damage; and 5) FXR can directly increase the expression of some tumor-suppressor genes and repress the transcription of several oncogenes. However, inflammation and epigenetic silencing are known to decrease FXR expression during tumorigenesis. The reactivation of FXR function in the liver may be a potential therapeutic approach for patients with liver cancer.